Analysis of Impact of Changes in IFRSs on Convergence of Accounting Systems in World - Shkulipa, Lyudmyla (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
The article examines the impact of updated IFRS on the current convergence of national accounting and reporting rules in Japan, the USA, China, France, Germany, the UK, and Ukraine based on a theoretical analysis of 59 rules and concepts of IFRS. The new differences between the updated IFRS and GAAP of these countries based on the comparative analysis were revealed. The results of the study show currently Ukraine (51%) and the United Kingdom (47%) are the most convergent with IFRS, although their degree of convergence has decreased significantly after recent innovations in IFRS; a new question arises for the UK after Brexit regarding the further application of IFRS; countries with strong national accounting traditions continue to avoid rapid changes in their GAAP; 4) the increase in the convergence of GAAP Japan with IFRS will not be possible shortly. The conclusion states that the main obstacle in the convergent process GAAP and IFRS is that: 1) IFRS are changing based on GAAP USA, rather than vice versa; 2) IFRS do not belong to the "stable to change standards", so users have a certain distrust of the declared high quality of IFRS. The study results add significant novelty to scientific and practical research on the impact of frequent changes in IFRS both locally and internationally.